Cameronaptera glabrinotum n.gen., n.sp. from Malaysia(Hemiptera: Heteroptera: Aradidae) - Heiss, E. (Zootaxa, 2010)
A new genus of apterous Carventinae from the Malaysian mainland, Cameronaptera n. gen. with the species glabrinotum n.sp., is described and figured. Because of its habitus and abdominal structures, it is not related to any other Oriental Carventinae.